Teaching Efficient Reading - Paul C. Berg (My University, 1977)
Comprehension in reading is the outcome of visual and perceptual skills and concept development. Critical reading is a refinement of comprehension skills, and flexible reading is the way in which all of these are brought together smoothly and effectively by the mature reader. The last chapter, 'Reading in the Content Areas' illustrates how the ideas developed in the earlier chapters may be applied to a particular discipline.
Keywords: English